Penerapan Dialog dan Interaksi Media Sosial dalam Konteks Komunikasi Interpersonal Guru dan Siswa di SMPN 13 Depok - Nuha Afifah Rubihalia; Muhammad Nabil Ramadhan; Diah Febrina (Journal of Community Service and Engagement, 2026)
This community-based empirical study examines the implementation of BERKATA (Bersama Komunikasi Merata), a participatory intervention integrating face-to-face dialogue and social media interaction to strengthen teacher–student interpersonal communication at SMPN 13 Depok. The program was initiated through a needs assessment using surveys and interviews to measure the magnitude of communication problems within the school community. Baseline findings indicated that communication issues were primarily caused by delayed information delivery (57.9%) and inadequate communication media (25.7%), leading to confusion and recurrent misunderstandings. The intervention was conducted over two weeks through two structured dialogue sessions and continuous interactive content dissemination via the school’s Instagram platform (@Galasresmi). Evaluation employed a mixed approach, combining post-program surveys, direct observation, social media engagement documentation, and brief interviews to capture behavioral and attitudinal changes. Results suggest a positive shift in communication openness and participation, where 53.3% of students agreed and 46.7% strongly agreed that the dialogue sessions increased their confidence to express communication concerns. Teachers also demonstrated improved receptiveness toward student feedback. The findings highlight the necessity of integrating relational and digital communication strategies to achieve sustainable improvements.